The market of own experience: Service user involvement and the commodification of individuals’ experience of mental illness (Sociologisk Forskning, 2019)
Recent research on user involvement in welfare services suggests that involvement practices are increasingly individualized and driven by market logics. This article is based on an ethnographic study within a public psychiatry organization, applying the concept of commodification to examine this trend in contemporary user involvement. By showing how public user involvement takes the form of a market where individuals’ narratives and experiences of mental health and psychiatric treatment are bought and sold as a commodity, the analysis illuminates how market logics manifests in practice. One of the consequences of this commodification is that the user movement and its representatives are limited in their role as independent actors pursuing their own agenda, instead acting increasingly on behalf of the public and as a supplier of personal experiences.
Keywords: narratives; service users involvement; commodification; experts by experience; mental health